Targeted lentiviral vectors pseudotyped with the Tupaia paramyxovirus glycoproteins - Enkirch, Theresa; Hoyler, Birgit; Ungerechts, Guy; Stremmel, Wolfgang; Springfeld, Christoph (Gene therapy, 2013)
Lentiviral vectors are vectors of choice for many gene therapy applications. Recently, efficient targeting of lentiviral vectors pseudotyped with the Measles virus (MV) glycoproteins has been reported. However, MV antibodies in patients might limit the clinical use of these vectors. We demonstrate here that lentiviral vectors can also be pseudotyped with the glycoproteins of Tupaia paramyxovirus (TPMV), the hemagglutinin (H) and fusion (F) protein. As this animal paramyxovirus has no known close relatives in humans, we do not expect TPMV antibodies in patients. Because TPMV normally does not infect human cells, ‘detargeting’ from natural receptors is unnecessary. Similar to the MV system, TPMV glycoproteins can mediate targeted cell entry by displaying different single-chain antibodies (scAb) directed against surface molecules on target cells on the viral hemagglutinin. We generated a panel of H and F proteins with truncated cytoplasmic tails and determined the variants that efficiently pseudotyped lentiviral vectors. The B-cell marker CD20 was used as a model antigen, and CD20-targeted TPMV vectors selectively transduced CD20-positive cells, including quiescent primary human B-cells. Lentiviral vectors pseudotyped with targeted TPMV envelope proteins might be a valuable vector choice when systemic application of targeted lentiviral vectors in humans is required.